Retinopathy of Prematurity – Bangladesh perspective (Northern International Medical College Journal, 2021)
Retinopathy of Prematurity (ROP) results in severe visual impairment and blindness in newborns. Now a days with the advancement of the technology to save preterm infants, its incidence is also increasing in both developed and developing countries. Appropriate and timely screening program can prevent ROP and reduces the functional impairment of eyes. Many countries have their guideline for ROP screening. Bangladesh national guideline is still in progress. Hope it will be published soon. In Bangladesh practically nationwide ROP screening was started in 2013. But still most of the screening program is limited to the capital city. Vast majority of neonates who stayed in peripheral districts are still out of screening program and failed to have timely referral. The current efforts of screening program are mainly driven by the private, NGO and the Gov’t professional bodies.Northern International Medical College Journal Vol.11 (2) Jan 2020: 447- 452